The Potential Utilization of Non-Productive Sugar Palm (Arenga pinnata Merr.) Trunks for Pulp and Bioenergy Applications - Rahmadani, Silmi Yusri; Alponsin; Dimas Surya Pratama; Tesri Maideliza (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2026)
The sugar palm (Arenga pinnata Merr.) has considerable potential as a biomass resource and as a raw material for pulp production. In West Sumatra, particularly in the Tanah Datar and Lima Puluh Kota regencies, cultivation areas cover approximately 376.75 ha and 285.00 ha, respectively. Although sap extraction for palm sugar and bioethanol remains the primary use, non-productive trunks are largely underutilized. This study evaluated the physical and chemical properties of these trunks, focusing on fiber dimensions, chemical composition, and calorific value. Trunks from Lima Puluh Kota exhibited longer fibers (2.70–2.97 mm), higher felting power (90.33), and favorable Runkel ratios, resulting in a Class I fiber quality rating for pulp production. In contrast, samples from Tanah Datar were classified as Class II. The trunks also showed cellulose contents ranging from 35.21% to 64.63% and moderate lignin levels (8.02–18.40%), both of which are advantageous for pulping. However, the calorific values (2,675–3,374 cal/g) were below national and international standards for biomass fuels. Overall, these findings suggest that non-productive sugar palm trunks are better suited for pulp and paper applications than for bioenergy production. Optimizing their use could support circular economy development while increasing value for local communities.